Risk Factors for Withdrawal of Life-Sustaining Treatment in Severe Traumatic Brain Injury. Issue 1 (January 2020) - Gambhir, Sahil; Grigorian, Areg; Ramakrishnan, Divya; Kuza, Catherine M.; Sheehan, Brian; Maithel, Shelley; Nahmias, Jeff
Studies demonstrate a significant variation in decision-making regarding withdrawal of life-sustaining treatment (WLST) practices for patients with severe traumatic brain injury (TBI). We investigated risk factors associated with WLST in severe TBI. We hypothesized age ≥65 years would be an independent risk factor. In addition, we compared survivors with patients who died in hospital after WLST to identify potential factors associated with in-hospital mortality. The Trauma Quality Improvement Program (2010–2016) was queried for patients with severe TBI of the head. Patients were compared by age (age < 65 and age ≥ 65 years) and survival after WLST (survivors versus non-survivors) at hospitalization discharge. A multivariable logistic regression model was used for analysis. From 1, 403, 466 trauma admissions, 328, 588 (23.4%) patients had severe TBI. Age ≥ 65 years was associated with increased WLST (odds ratio: 1.76, confidence interval: 1.59–1.94, P < 0.001), whereas nonwhite race was associated with decreased WLST (odds ratio: 0.60, confidence interval: 0.55–0.65, P < 0.001). Compared with non-survivors of WLST, survivors were older (74 vs 61 years, P < 0.001) and more likely to have comorbidities such as hypertension (57% vs 38.5%, P < 0.001). Age ≥ 65 years was an independent risk factor for WLST, and nonwhite race was associated with decreased WLST. Patients surviving until discharge after WLST decision were older (≥74 years) and had multiple comorbidities.